EFEKTIVITAS PENGGUNAAN MODUL TERHADAP HASIL BELAJAR MATEMATIKA KOMPUTASI PADA MAHASISWA TEKNIK INFORMATIKA - Filda Febrinita (De Fermat : Jurnal Pendidikan Matematika, 2022)
In computational mathematics learning which is carried out online, students experience obstacles in the process of understanding the material. The results of the UAS showed that 16 out of 30 students or 53% of students did not achieve the minimum specified learning completion, which was 75. Therefore, learning is carried out by applying modules to computational mathematics courses. Through modules, students can measure the speed and intensity of their learning and get used to learning effectively and systematically. Modules can train students to learn independently while developing literacy skills. Based on the identification of problems, research was carried out with the design of one group pretest-posttest design to find out and measure the effectiveness of the use of modules on computational mathematics learning outcomes in informatics engineering students. The study population was 30 students with saturated sampling techniques. The  for pretest and posttest data is 0.58 or 57.99%, which means that the effectiveness of using modules in computational mathematics learning is in the medium category or is in a fairly effective interpretation. The result of the significance value for the  with SPSS shows the significance value is 0.000. Since the significance value is less than 0.5 then  rejected. Based on the results of these tests, it can be concluded that the use of modules in learning computational mathematics in students of the informatics engineering study program, FTI Unisba Blitar, has been tested effectively with the category of increasing learning outcomes being moderate.